Rough set for predicting the Kuala Lumpur Stock Exchange Composite Index returns [electronic resource] - 339160 Kok, Yit Pong (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Sarjana Muda Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2004